2014
DOI: 10.1111/cag.12066
|View full text |Cite
|
Sign up to set email alerts
|

Oil and gas infrastructure and the spatial pattern of grizzly bear habitat selection in Alberta, Canada

Abstract: Oil and gas development is increasing in areas of Alberta, Canada that are also home to threatened grizzly bear (Ursus arctos) populations. While impacts of forest disturbances on bears have been heavily studied, research on the impacts of oil and gas activities is limited. Our research goal was to test the hypothesis that grizzly bears select locations of oil and gas development randomly, using grizzly bear telemetry data collected from 2005 to 2010 in the Kakwa region of Alberta. Maps of probability of resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…In the current study, the stress response of grizzly bears was associated with variables representative of anthropogenic disturbance, with a reduction in HCC as the density of oil and gas well-sites increased and an elevation in HCC as the distance to coal mines increased. While bears have been shown to avoid active well-sites and oil and gas features during the summer and fall seasons (Laberee et al 2014), they were also more likely to be detected near oil and gas well-sites in our study area, especially if food availability was low in the surrounding areas (Rovang et al 2015). Grizzly bears have also shown selection for well-sites (McKay et al 2014), and this may be because these areas provide a concentrated source of bear foods at the well-site edges.…”
Section: Discussionmentioning
confidence: 77%
“…In the current study, the stress response of grizzly bears was associated with variables representative of anthropogenic disturbance, with a reduction in HCC as the density of oil and gas well-sites increased and an elevation in HCC as the distance to coal mines increased. While bears have been shown to avoid active well-sites and oil and gas features during the summer and fall seasons (Laberee et al 2014), they were also more likely to be detected near oil and gas well-sites in our study area, especially if food availability was low in the surrounding areas (Rovang et al 2015). Grizzly bears have also shown selection for well-sites (McKay et al 2014), and this may be because these areas provide a concentrated source of bear foods at the well-site edges.…”
Section: Discussionmentioning
confidence: 77%
“…Grizzly bears in Alberta occupy a multi-use landscape, resulting in complex spatial associations among anthropogenic disturbance features, habitat characteristics and body condition. For example, forest harvest blocks and oil and gas well sites that create access to herbaceous foods ( Nielsen et al , 2004a , c ; Laberee et al , 2014 ) provided gains in body condition. Likewise, regenerating forest conditions, which are generally associated with anthropogenic rather than natural disturbances in Alberta, allowed bears to improve body condition.…”
Section: Discussionmentioning
confidence: 99%
“…Habitat selection by grizzly bears within a multi-use heterogeneous landscape is complex ( Nielsen et al , 2002 ). A number of studies have shown that grizzly bears in Alberta select areas associated with anthropogenic disturbance and edge habitats, such as roads, pipelines, forest harvest blocks and oil and gas well sites ( Nielsen et al , 2004a ; Berland et al , 2008 ; Graham et al , 2010 ; Stewart et al , 2013 ; Laberee et al , 2014 ). While selection of anthropogenic features has been found to vary according to grizzly bear age and gender in Alberta (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Industrial activities can change the spatial distribution of foods potentially placing bears at risk, for example, if natural foods become available close to humans (Roever et al 2008) or if bears seek human-sourced foods on industrial sites (McLellan 1990). Reproductive classes and individual bears can vary in their behaviour in relation to extractive industries such as logging (Roever et al 2008) and oil and gas (Laberee et al 2014).…”
Section: Introductionmentioning
confidence: 99%